Seasonal Variation of White Clover Morphology at the North of Buenos Aires Province, Argentine - Pagano, Elba Maria (2001)
In order to study the seasonal variation in morphological characters that contribute to forage production in white clover (Trifolium repens L.) cultivars, a trial was conducted at Pergamino Agricultural Experimental Station INTA located north of Buenos Aires province, Argentina. The experimental plots were set out in a completely randomized design with four replicates. Measurements were performed over eight seasons throughout two years. The used cultivars had been previously reported as having differences in seasonal productivity. Significant differences were detected among seasons for all measured characters i. e. stolon length, number of buds, branches and leaves, and leaf area. Differences among cultivars in almost all the season were only found for leaf area and stolon length. The growth in length of stolons kept a consistent pattern in both years. No cultivar produced vegetative buds during summers. The characters most affected by environmental stress were bud and branch development. Keywords: Trifolium repens L., morphological characters, seasonal variation, cultivars.